Hydrobiology of the mangal : (W. Junk, 1984)
In almost all studies of mangrove ecosystems the role of zooplankton has been neglected or memtioned only brielfy. This is uderstandable in view of the concentration of most studies on the mangroves and their productivity, or the associated benthic fauna.